Collaborative Key Exchange System Based on Chinese Remainder Theorem in Heterogeneous Wireless Sensor Networks - Mohamed Kasraoui; Adnane Cabani; Houcine Chafouk (International Journal of Distributed Sensor Networks)
IPv6 over Low Power Wireless Personal Area Networks (6LoWPANs), in the next generation of wireless sensor networks, represent an emerging field which can be integrated with Internet technology. Security is one of the most important issues in 6LoWPANs given the vulnerability to security threats from Internet and the inherent constraints such as bandwidth, processing power, memory, and energy. Despite limited resources, data security for nodes adds an additional heavy cost by using various security schemes. Moreover, there is no standard approach to provide the end-to-end security in 6LoWPANs. In this work, we first axed our research to propose a new end-to-end security scheme for IP enabled sensor networks to optimize battery energy consumption and then we adapted the Internet Key Exchange version 2 (IKEv2) to wireless sensor networks while taking into consideration the scarce resources. Hence a novel Cooperative Key Exchange System (CKES) has been proposed in this paper based on Chinese Remainder Theorem (CRT) which has also been implemented in NS2 to analyze energy consumption compared to IKEv2.